2022
DOI: 10.1177/15330338221086403
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies and Prognostic Factors of 2018 FIGO Stage IIIC Cervical Cancer: A Review

Abstract: Cervical cancer is the fourth most common malignant tumor globally in terms of morbidity and mortality. The presence of lymph node metastasis (LNM) is an independent prognostic factor for progression-free survival (PFS) and overall survival (OS) in cervical cancer patients. The International Federation of Gynecology and Obstetrics (FIGO) staging system was revised in 2018. An important revision designates patients with regional LNM as stage IIIC, pelvic LNM only as stage IIIC1, and para-aortic LNM as stage III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 119 publications
1
7
0
Order By: Relevance
“… 16 Up till now, CCRT was generally considered the primary treatment choice for stages IB2, IIA2, and IIB to IVA cervical cancer. 43 , 44 Kim et al reported that 52% patients with left supraclavicular and paraaortic LN metastases could achieve complete response from CCRT. 36 A prospective observational study revealed that CCRT induces increased infiltration of CD8 + T cells and activation of IFN signaling, indicating great promise for the combination of immunotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Up till now, CCRT was generally considered the primary treatment choice for stages IB2, IIA2, and IIB to IVA cervical cancer. 43 , 44 Kim et al reported that 52% patients with left supraclavicular and paraaortic LN metastases could achieve complete response from CCRT. 36 A prospective observational study revealed that CCRT induces increased infiltration of CD8 + T cells and activation of IFN signaling, indicating great promise for the combination of immunotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, cervical cancer ranks as the fourth most frequently occurring malignancy among women population. 1 Over 500,000 women worldwide are diagnosed with cervical cancer each year, with low-income nations bearing the burden of mortality. 2 Nearly all cervical malignancies contain oncogenic human papillomavirus (HPV) DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The most important staging system for CC is the International Federation of Gynecology and Obstetrics (FIGO) staging. Several studies have demonstrated lymph node metastasis (LNM) to be a poor prognostic factor [2][3][4][5]; therefore, FIGO staging elevated CC with metastatic lymph…”
Section: Introductionmentioning
confidence: 99%